Using serial bluetooth converters as a sensor link in networked control systems - Godoy, Eduardo P. [UNESP]; Scorzoni, Fernando; Tangerino, Giovana T.; Porto, Arthur J.V.; Inamasu, Ricardo Y. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Networked control systems (NCS) are distributed control system in which sensors, actuators and controllers are physically separated and connected through communication networks. NCS represent the evolution of networked control architectures providing greater modularity and control decentralization, ease maintenance and diagnosis and lower cost of implementation. A recent trend in this research topic is the development of NCS using wireless networks which enable interoperability between existing wired and wireless systems. This paper presents the feasibility analysis of using a serial RS-232 to Bluetooth converter as a wireless sensor link in NCS. In order to support this investigation, relevant performance metrics for wireless control applications such as jitter, time delay and messages lost are highlighted and calculated to evaluate the converter capabilities. In addition the control performance of an implemented motor control system using the converter is analyzed. Experimental results led to the conclusion that serial RS-232 Bluetooth converters can be used to implement wireless networked control systems (WNCS) providing transmission rates and closed control loop times which are acceptable for NCS applications. © 2011 IEEE.
Keywords: Closed control loop; Control performance; Feasibility analysis; Lower cost; Motor control system; Networked control system (NCS); Networked controls; Performance metrics; Recent trends; Research topics; Transmission rates; Wired and wireless; Wireless control; Wireless networked control systems; Wireless sensor; Bluetooth; Interoperability; Networked control systems; Sensors; Wireless networks; Delay control systems